REDISCUSSION OF PER100 CHANGE OF THE CLOSE BINARY V65l CASSIOPEIAE - Chun-Hwey Kim; Jae Woo Lee; Chung Uk Lee; Dong Ju Lee; Young Woon Kang (Journal of Astronomy and Space Sciences, 2002)
Observations of times of minimum lights of the eclipsing binary V65l Cas were carried out on the three nights from November 21-23, 2000. From our observations a total of seven new times of minimum lights was obtained. Through the analysis of photoelectric and CCD times of minima of V65l Cas including ours, the light time orbit due to a third body, which was propose by Kim ＆ Lee (2000), was confirmed and improved. The resultant values for the period, semi-amplitude, and eccentricity of the light-time orbit were 6.y3, 0.d0013, and 0.78, respectively. The deduced marts range of the third body is. If the third body is 0.09 M⨀ ≤ M3 ≤ 0.20 M⨀ foor i3 ≥ 30˚. If the third body suggested in V65l Cas system exists really and is a main-sequence star, it is located at the end of the main-sequence.